Phylogeny of asian homalomena (Araceae) based on the its region combined with morphological and chemical data - Wong, Sin Yeng; Tan, Pei Jean; Ng, Kiaw Kiaw; Ahmad, S. Othman; Lee, Hong Boon; Fasihuddin, Badruddin Ahmad; Boyce, P.C (American Society of Plant Taxonomists Inc., 2013)
A phylogenetic analysis of the genus Homalomena (Araceae: Homalomeneae) based on the nITS region is presented. Eighty-nine taxa are included; representing all Asian supergroups, several Neotropical species currently assigned to Homalomena, and selected species of Philodendron. Asian Homalomena is well supported as monophyletic and excludes Neotropical Homalomena. The Cyrtocladon supergroup is monophyletic after transferring the Insignis complex and Havilandii complex into the Punctulata supergroup. The Homalomena and Chamaecladon supergroups are well supported. A reduced phylogeny of 20 accessions representing 15 taxa was used for subsequent morphological and chemical marker optimization. A constricted spathe and four stamens per staminate flower are plesiomorphic for Homalomena. Staminodes among the pistillate zone are lost three times independently in Homalomena supergroup, Punctulata supergroup, and H. vivens. Chemical markers identified from liquid chromatography-mass spectroscopy profiling provided an independent set of markers that further support the separation of Neotropical species of Homalomena from the Asian taxon. Three chemical markers at Rt 2.55 min, 2.69 min, and 2.90 min are shared among the majority of taxa sampled for Asian Homalomena, and Neotropical species currently assigned to Homalomena show two unique peaks at Rt 3.25 min and 3.54 min. Five chemical markers support the Cyrtocladon supergroup with the exception of Homalomena vivens. A chemical marker at Rt 3.60 min is plesiomorphic for the Chamaecladon, Homalomena and Punctulata supergroups. A chemical marker at Rt 2.80 min is apomorphic for the Chamaecladon supergroup, with a separate gain in H. punctulata. This study supports removal of the Neotropical species from Homalomena, redefines the morphological boundaries of Homalomena sensu stricto (i.e. the Asian species), and supports and refines the grouping of Asian species into supergroups.